2007
DOI: 10.3354/meps329115
|View full text |Cite
|
Sign up to set email alerts
|

Temperature affects coral disease resistance and pathogen growth

Abstract: Temperature anomalies on coral reefs now routinely exceed coral stress thresholds, making temperature a critical variable to consider in coral host -pathogen systems. While temperature is widely hypothesized to drive coral disease outbreaks by decreasing coral resistance and increasing pathogen growth rates, tests of the temperature hypothesis are rare. Here we report evidence from the sea fan coral Gorgonia ventalina -Aspergillus host -pathogen system that temperature stress increases one component of sea fan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 30 publications
3
106
0
Order By: Relevance
“…Furthermore increasing water temperatures in reef environments allow pathogens to expand their ecological thermal disease in starfishniche, for example by colonizing low pH environments (Remily & Richardson, 2006). Although thermal stress can induce higher levels of resistance in the host, the growth rate of pathogenic bacteria can increase, and an infection become established before host resistance is maximal (Ward, 2007). In contrast to the numerous tropical reef studies of sessile species, relatively little information exists about thermal induced diseases and potential pathogens in temperate mobile invertebrate populations (Eckert, 2000;Farto et al, 2003;Becker et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore increasing water temperatures in reef environments allow pathogens to expand their ecological thermal disease in starfishniche, for example by colonizing low pH environments (Remily & Richardson, 2006). Although thermal stress can induce higher levels of resistance in the host, the growth rate of pathogenic bacteria can increase, and an infection become established before host resistance is maximal (Ward, 2007). In contrast to the numerous tropical reef studies of sessile species, relatively little information exists about thermal induced diseases and potential pathogens in temperate mobile invertebrate populations (Eckert, 2000;Farto et al, 2003;Becker et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Lawrence, 2004;Sabaté, 2006;Ward et al, 2007;Webster, 2007). A majority of these studies deal with mass mortalities observed in different coral species and other sessile invertebrates (Perez et al, 2000;Kushmaro et al, 2001;Boyett et al, 2007;Remily & Richardson, 2006;Ward et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental stress impairs coral host immunity and promotes pathogen virulence (Fitt et al 2001, Blanford et al 2003, Lafferty & Holt 2003, Ward et al 2007). As such, disease prevalence (predominantly tissue loss diseases) often increases during or proceeding coral bleaching events when temperatures are high and the coral hosts are compromised (Jones et al 2004b, Miller et al 2006, Whelan et al 2007, Brandt & McManus 2009, Bruckner & Hill 2009, Cróquer & Weil 2009).…”
Section: Disease Severity Fate and Temporal Patternsmentioning
confidence: 99%
“…Nevertheless, fungi that are known to cause marine diseases can thrive in unusually high temperatures. One example of this is A. sydowii which causes asperillosis, a disease of G. ventalina (Ward et al 2007). This disease has become epidemic in sea fan populations in the Caribbean with the warming of ocean temperatures in mid-summer to over 30°C.…”
Section: Effects Of the Environment On Diseases Of Corals And Molluscsmentioning
confidence: 99%